2021
DOI: 10.1021/acscatal.1c01061
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Insights into the Active Sites on WOx/Pt(111) Surfaces for Dehydrogenation and Dehydration Reactions

Abstract: The catalytic upgrading of biomass is an important step toward realizing renewable chemical production. Pt/WO x and the inverse catalyst, WO x /Pt, have been shown to be highly active and selective for the C−O bond scission of various biomassderived oxygenates. Yet, the nature of the active sites and detailed reaction mechanisms have not been well understood. In this study, carbon monoxide and isopropyl alcohol (IPA) have been used as probe molecules to study the active sites of WO x /Pt(111) model surfaces. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…5. Surface oxygen vacancies of plasmonic W 18 O 49 -NWs can absorb H 2 O molecules to form OH moieties as Brønsted acid sites which are active in catalyzing isopropanol dehydration for propylene 12,28 . When isopropanol molecules diffuse to the surface of W 18 O 49 -NWs, they are coordinated to OH groups by hydroxyl accepted a proton.…”
Section: Catalytic Mechanism Of the Isopropanol Dehydration Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Surface oxygen vacancies of plasmonic W 18 O 49 -NWs can absorb H 2 O molecules to form OH moieties as Brønsted acid sites which are active in catalyzing isopropanol dehydration for propylene 12,28 . When isopropanol molecules diffuse to the surface of W 18 O 49 -NWs, they are coordinated to OH groups by hydroxyl accepted a proton.…”
Section: Catalytic Mechanism Of the Isopropanol Dehydration Reactionmentioning
confidence: 99%
“…Gallium borates with Brønsted acid sites were reported to show 98.3% conversion of isopropanol to 100% propylene at 573 K 11 . Chen et al studied the active sites on the WO x /Pt (111) surface for the dehydration and dehydrogenation of isopropanol, demonstrating dominant dehydration reaction on W 3 O 9 clusters with an activation barrier of 1.23 eV 12 . However, all these reports showed that a high temperature was required to active the catalysts and that the reactions were associated with high activation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Another research team 68 postulated that there was a strong correlation between the selectivity of dehydrogenation of IPA and the redox couple species evaluated on LaCoO 3 catalyst. To support their proposed mechanism, Lin et al 69 employed density functional theory (DFT) to calculate the activation barrier of dehydrogenation and dehydration reactions of IPA over WO x /Pt (111) surfaces. In the case of 2B, we had previously attributed the dehydrogenation activity of NiO, whether pure or modified with K 2 O or F‐ions, during dehydrogenation of 2B to MEK to the presence of basic sites of varying strengths 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…The WO x /Pt catalysts were represented by W 3 O x trimers on a 5 × 4 Pt(111) slab following prior work by Lin et al DFT calculations were performed using the Perdew–Burke–Erzenhof exchange-correlation function as implemented in version 5.4 of the Vienna Ab initio Simulation Package (VASP) with the projector augmented wave method (PAWs) used to describe core electrons. The plane-wave energy cutoff was set to 520 eV.…”
Section: Methodsmentioning
confidence: 99%